Efficacy of NAMPT inhibition in T-cell acute lymphoblastic leukemia - Chelsea Vrana; Matthew Zhang; Max Rochette; Michelle Alozie; Hailey Oviedo; Alan Gonzalez; Jaden Sherman; Barry Zorman; Pavel Sumazin; Karen R. Rabin; Jacob J. Junco (PLoS ONE, 2025)
Novel agents targeting upregulated signaling pathways are needed to improve outcomes in T-cell acute lymphoblastic leukemia (T-ALL), since conventional cytotoxic chemotherapy regimens have reached the limits of tolerability. We identified upregulated, targetable signaling pathways common to both human T-ALL samples and a KrasLSL-G12D/+.Mb1Cre/+ murine model of T-ALL. We found the NAMPT inhibitor FK866 had the greatest cytotoxicity of a panel of small molecule inhibitors tested in human and mouse T-ALL cell lines, and in patient derived xenograft (PDX)-expanded T-ALL patient samples. We subsequently tested FK866 in vivo in PDX mouse models of T-ALL, and found that it significantly reduced the peripheral blood disease burden and prolonged the survival of leukemic mice (median survival of 60.5 vs 21 days, p = 0.0007). This screen for targetable pathways in T-ALL generated in vitro and in vivo preclinical data supporting NAMPT inhibition as a promising strategy for the treatment of T-ALL.